2015
DOI: 10.1177/0267659115618460
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr futile myocarditis requiring urgent orthotopic heart transplantation

Abstract: We present the case of a 37-year-old man who was diagnosed with an Epstein-Barr futile myocarditis. The diagnosis was made in the Accident and Emergency Department, with the input of portable echocardiography. The patient subsequently underwent an urgent orthotopic heart transplantation and he has now completely recovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, a chronic active Epstein-Barr virus (CAEBV) infection characterized by high EBV DNA levels in the peripheral blood (Kawabe et al, 2018) can cause organ damage demonstrated by endomyocardial biopsies with lymphocytic infiltration, necrosis of cardiomyocytes et cetera and end up in a chronic active myocarditis (Takano et al, 2008). Sometimes, an Epstein-Barr myocarditis (Antonakaki et al, 2016) is so severe that an urgent orthotopic heart transplantation is necessary. Finally, Aghenta et al (Aghenta et al, 2008) published the case of a 19-year-old healthy male patient presented to hospital with clinical features of infectious mononucleosis (IM).…”
Section: Discussionmentioning
confidence: 99%
“…However, a chronic active Epstein-Barr virus (CAEBV) infection characterized by high EBV DNA levels in the peripheral blood (Kawabe et al, 2018) can cause organ damage demonstrated by endomyocardial biopsies with lymphocytic infiltration, necrosis of cardiomyocytes et cetera and end up in a chronic active myocarditis (Takano et al, 2008). Sometimes, an Epstein-Barr myocarditis (Antonakaki et al, 2016) is so severe that an urgent orthotopic heart transplantation is necessary. Finally, Aghenta et al (Aghenta et al, 2008) published the case of a 19-year-old healthy male patient presented to hospital with clinical features of infectious mononucleosis (IM).…”
Section: Discussionmentioning
confidence: 99%
“…This immune-mediated damage may be led by CD8 + T cells [81]. Reported cases, although rare, have generally been severe, even requiring heart transplantation, although this may reflect an underreporting of the subclinical presence of EBV in the heart [150]. Electron microscopy studies have revealed the presence of EBV antigens in cardiomyocytes and intramural vessels of patients with myocarditis and DCMi, despite the virus' general tropism for B lymphocytes [82,83].…”
Section: Herpesviridaementioning
confidence: 99%
“…An acute case of EBV-induced heart inflammation has been previously associated with the presence of lymphocytic infiltrates and a T cell marker CD 45 R0 ( Ishikawa et al, 2005 ). The disease severity progression and the outcome vary among patients, and in some cases symptoms can resolve on their own, whereas in others the heart becomes irreversibly damaged, resulting in a patient’s death ( Ishikawa et al, 2005 ; Antonakaki et al, 2016 ). Reactivation of the virus after the initial infection has also been previously reported, as shown by the presence of EBV-encoded RNA and mononuclear infiltrates in the pericardium ( Richter et al, 2013 ).…”
Section: Herpesvirusesmentioning
confidence: 99%